2004
DOI: 10.1161/01.cir.0000121739.05643.e6
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Clopidogrel Combined With Aspirin in Reducing Cerebral Emboli in Patients Undergoing Carotid Endarterectomy

Abstract: Background-Postoperative thromboembolic stroke affects 2% to 3% of patients undergoing carotid endarterectomy (CEA) and is preceded by 1 to 2 hours of increasing cerebral embolization. Previous work has demonstrated that high rates of postoperative embolization are associated with increased platelet reactivity to adenosine 5Ј-diphosphate (ADP). Our hypothesis was that preoperative administration of the platelet ADP antagonist clopidogrel could reduce postoperative embolization. Methods and Results-One hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 212 publications
(133 citation statements)
references
References 28 publications
3
127
0
3
Order By: Relevance
“…We subsequently showed that a submaximal dose of clopidogrel (75 mg), given with aspirin, before carotid surgery resulted in a significant reduction in postoperative embolization (thus reducing the risk of postoperative embolic stroke) without a real increase in bleeding. 15 The question addressed here is how this low dose of clopidogrel can produce such an effective clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We subsequently showed that a submaximal dose of clopidogrel (75 mg), given with aspirin, before carotid surgery resulted in a significant reduction in postoperative embolization (thus reducing the risk of postoperative embolic stroke) without a real increase in bleeding. 15 The question addressed here is how this low dose of clopidogrel can produce such an effective clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…All patients enrolled were on long-term aspirin therapy, standardized to 150 mg aspirin for 4 weeks before surgery. The methodology has been described previously 15 and was a double-blind randomized control trial with patients receiving either a single 75-mg dose of clopidogrel or placebo 12 hours before surgery in addition to their aspirin. Patients were excluded from the trial if they had refused informed consent, reported aspirin intolerance, had not complied with aspirin administration, or were already taking other antiplatelet or antithrombotic therapy.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations